In Vitro Antimicrobial Activities of Fusidic Acid and Retapamulin against Mupirocin- and Methicillin-Resistant Staphylococcus aureus - Park, Sang Hyun (Ann Dermatol, 2015)
BACKGROUND: The in vitro activities of retapamulin and fusidic acid against clinical isolates of mupirocin-resistant and methicillin-resistant Staphylococcus aureus (MRSA) from Korea are not well understood. OBJECTIVE: This study aimed to determine the activities of retapamulin and fusidic acid against clinical isolates of mupirocin-resistant MRSA. METHODS: Clinical isolates of mupirocin-resistant MRSA were collected from two tertiary hospitals. The minimal inhibitory concentrations of mupirocin, fusidic acid, and retapamulin were determined using agar dilution method. Polymerase chain reaction was used to confirm the identity of the species and the presence of resistance genes. Pulsed-field gel electrophoresis (PFGE) patterns of chromosomal DNA were used to determine the genetic similarity of high-level mupirocin-resistant isolates. RESULTS: Of the 497 MRSA isolates tested, 22 (4.4%) were mupirocin-resistant. Of these, 9 (1.8%) and 13 (2.6%) had high-level and low-level mupirocin resistance, respectively. Analysis of the PFGE patterns of the high-level mupirocin-resistant MRSA isolates identified five clusters. All 13 of the low-level mupirocin-resistant isolates were resistant to fusidic acid but susceptible to retapamulin. However, among the 9 high-level mupirocin-resistant isolates, 56% were resistant to fusidic acid, and all were susceptible to retapamulin. CONCLUSION: Retapamulin is highly active in vitro against Korean clinical isolates of high-level mupirocinand methicillin-resistant Staphylococcus aureus with different genetic backgrounds. Fusidic acid is more active against high-level mupirocin-resistant MRSA than low-level mupirocin-resistant MRSA.